2021
DOI: 10.1186/s12859-021-04446-4
|View full text |Cite
|
Sign up to set email alerts
|

ReRF-Pred: predicting amyloidogenic regions of proteins based on their pseudo amino acid composition and tripeptide composition

Abstract: Background Amyloids are insoluble fibrillar aggregates that are highly associated with complex human diseases, such as Alzheimer’s disease, Parkinson’s disease, and type II diabetes. Recently, many studies reported that some specific regions of amino acid sequences may be responsible for the amyloidosis of proteins. It has become very important for elucidating the mechanism of amyloids that identifying the amyloidogenic regions. Accordingly, several computational methods have been put forward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 75 publications
(86 reference statements)
0
14
0
Order By: Relevance
“…Using the PseAAC and TPC, the authors demonstrated and developed an accessible ReRF-Pred, a revolutionary machine-learning for predicting amyloidogenic regions. The authors specifically examined all possible tripeptides with binomial distribution, focusing on those with significantly different distributions between positive and negative samples [13]. PredAmyl-MLP and RFAmyloid train on a dataset consisting of 165 amyloid proteins and 382 non-amyloid sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the PseAAC and TPC, the authors demonstrated and developed an accessible ReRF-Pred, a revolutionary machine-learning for predicting amyloidogenic regions. The authors specifically examined all possible tripeptides with binomial distribution, focusing on those with significantly different distributions between positive and negative samples [13]. PredAmyl-MLP and RFAmyloid train on a dataset consisting of 165 amyloid proteins and 382 non-amyloid sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to the fine-tuning step, we were able to identify the following classifiers configurations capable of overcoming inaccuracy in the performance reported in [13]:…”
Section: Classifiers Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the convenience and high efficiency, computational methods are a good choice for identifying IBPs. Many machine learning algorithms, such as support vector machine (SVM) [10] , [11] , [12] , deep learning (DL) [13] , [14] , [15] , [16] , [17] , [18] , [19] , extreme boosting algorithm (XGBoost) [20] , [21] , [22] , [23] , [24] , and stacking ensemble models [25] , [26] , [27] , [28] , [29] , [30] , etc., have been developed for protein function, structure, subcellular localization, and even other biological processes. Different feature descriptors such as amino acid composition (AAC) [31] , [32] , [33] , reduced amino acid composition [34] , [35] , [36] , g -gap dipeptide composition [37] , [38] , and secondary structure features [39] , etc., were adopted to represent protein sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Teng et al [ 16 ] presented and created an accessible ReRF-Pred, a novel machine-learning based on a multi-feature encoding strategy for predicting amyloidogenic regions, using the pseudo amino acid composition (PseAAC) [ 17 ] and tripeptides composition (TPC) [ 18 ]. They obtained an accuracy, specificity, sensitivity and MCC of 80.10%, 83.1%, 73.4% and 0.552, respectively.…”
Section: Introductionmentioning
confidence: 99%